Rancang Bangun Sistem Penjadwalan Pengambilan Sampah Menggunakan PHP dan MySQL pada Dinas Lingkungan Hidup Kabupaten Sumba Barat - Maria Mala Rade; Yulius Nahak Tetik; Mitra Permata Ayu (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to design and develop a web-based waste collection scheduling system using PHP and MySQL at the Environmental Agency of West Sumba Regency. The main problem faced is that the scheduling process is still carried out manually, resulting in inefficiency, susceptibility to errors, and difficulties in monitoring and reporting. The system development method used is the Waterfall model, which includes requirement analysis, system design, implementation, testing, and maintenance stages. The developed system provides features for managing data on personnel, regions, vehicles, and structured waste collection scheduling. In addition, the system is equipped with notification features, schedule monitoring, and performance reporting that can be accessed by management. The results of this study indicate that the system improves effectiveness and efficiency in scheduling processes and facilitates supervision of waste collection activities. Therefore, the implementation of this system is expected to optimize and organize waste management in West Sumba Regency.